High‐mobility group box 1 emerges as a therapeutic target for asthma - Qianni Yang; Min Li; Yunjiao Hou; Huilin He; Shibo Sun (Immunity, Inflammation and Disease, 2023)
Abstract High‐mobility group box 1 (HMGB1) is a highly conserved nonhistone nuclear protein found in the calf thymus and participates in a variety of intracellular processes such as DNA transcription, replication and repair. In the cytoplasm, HMGB1 promotes mitochondrial autophagy and is involved in in cellular stress response. Once released into the extracellular, HMGB1 becomes an inflammatory factor that triggers inflammatory responses and a variety of immune responses. In addition, HMGB1 binding with the corresponding receptor can activate the downstream substrate to carry out several biological effects. Meanwhile, HMGB1 is involved in various signaling pathways, such as the HMGB1/RAGE pathway, HMGB1/NF‐κB pathway, and HMGB1/JAK/STAT pathway, which ultimately promote inflammation. Moreover, HMGB1 may be involved in the pathogenesis of asthma by regulating downstream signaling pathways through corresponding receptors and mediates a number of signaling pathways in asthma, such as HMGB1/TLR4/NF‐κB, HMGB1/RAGE, HMGB1/TGF‐β, and so forth. Accordingly, HMGB1 emerges as a therapeutic target for asthma.